Inverse Nodal Problem for Polynomial Potentials. (15th June 2021) - Koyunbakan, Hikmet; Shieh, Chung-Tsun
Abstract: In this work, we study an inverse nodal problem for a differential pencil with boundary condition depends on eigenparameter. We show that there exists a solution of the problem that satisfied the conditions. Also, we give eigenvalues, nodal points and some formulas for q n ( x ) . Although there were given some results for this type problem, we think that inverse nodal problems have not solved yet.